Structural insights into eukaryotic DNA replication - Doublié, Sylvie; Zahn, Karl E. (Frontiers in Microbiology, 2014)
Three DNA polymerases of the B family function at the replication fork in eukaryotic cells: DNA polymerases α, δ, and ε. DNA polymerase α, an heterotetramer composed of two primase subunits and two polymerase subunits, initiates replication. DNA polymerases δ and ε elongate the primers generated by pol α. The DNA polymerase from bacteriophage RB69 has served as a model for eukaryotic B family polymerases for some time. The recent crystal structures of pol δ, α, and ε revealed similarities but also a number of unexpected differences between the eukaryotic polymerases and their bacteriophage counterpart, and also among the three yeast polymerases. This review will focus on their shared structural elements as well as the features that are unique to each of these polymerases.